Cushing disease in pediatrics: an update - Marcio José Concepción-Zavaleta; Cristian David Armas; Juan Eduardo Quiroz-Aldave; Eilhart Jorge García-Villasante; Ana Cecilia Gariza-Solano; María del Carmen Durand-Vásquez; Luis Alberto Concepción-Urteaga; Francisca Elena Zavaleta-Gutiérrez (Korean Society of Pediatric Endocrinology, 2023)
Cushing disease (CD) is the main cause of endogenous Cushing syndrome (CS) and is produced by an adrenocorticotropic hormone (ACTH)-producing pituitary adenoma. Its relevance in pediatrics is due to the retardation of both growth and developmental processes because of hypercortisolism. In childhood, the main features of CS are facial changes, rapid or exaggerated weight gain, hirsutism, virilization, and acne. Endogenous hypercortisolism should be established after exogenous CS has been ruled out based on 24-hour urinary free cortisol, midnight serum or salivary cortisol, and dexamethasone suppression test; after that, ACTH dependence should be established. The diagnosis should be confirmed by pathology. The goal of treatment is to normalize cortisol level and reverse the signs and symptoms. Treatment options include surgery, medication, radiotherapy, or combined therapy. CD represents a challenge for physicians owing to its multiple associated conditions involving growth and pubertal development; thus, it is important to achieve an early diagnosis and treatment in order to control hypercortisolism and improve the prognosis. Its rarity in pediatric patients has led physicians to have limited experience in its management. The objective of this narrative review is to summarize the current knowledge about the pathophysiology, diagnosis, and treatment of CD in the pediatric population.